SURFACE MASS BALANCE, SUBLIMATION AND SNOW TEMPERATURES AT DOME FUJI STATION, ANTARCTICA, IN 1995 - カメダ, タカオ; アズマ, ノブヒコ; フルカワ, テルオ; アゲタ, ユタカ; タカハシ, シュウヘイ; KAMEDA, Takao; AZUMA, Nobuhiko; FURUKAWA, Teruo; AGETA, Yutaka; TAKAHASHI, Shuhei (National Institute of Polar Research, 1997)
P(論文) This paper focuses on the first year-round observations of surface mass balance, sublimation and snow temperatures at Dome Fuji Station. This station was newly established at the highest point (77°19′01″S, 39°42′12″E; 3810m) in Queen Maud Land, Antarctica by the Japanese Antarctic Research Expedition. It was found that average surface mass balance by the stake method was +2.5g(cm)^<-2> from 25 January 1995 to 30 January 1996 (370 days), of which about 95% of the positive balance was obtained from February to the middle of October (eight and half months). Sublimation from atmosphere to snow surface (mass input : +0.55g(cm)^<-2>) was predominant in winter (March to October) and sublimation from snow surface to atmosphere (mass output : -0.39g(cm)^<-2>) was predominant in summer (November to February). In the annual balance, sublimation from atmosphere to snow surface (+0.16g(cm)^<-2>) prevailed. This corresponds to about 6% of the annual surface mass balance. The snow temperature at 10m depth varied from -57.0 to -57.8℃, and the annual mean 10m snow temperature was -57.3℃. departmental bulletin paper